2018
DOI: 10.3389/fnhum.2018.00235
|View full text |Cite
|
Sign up to set email alerts
|

Somatotopy in the Human Somatosensory System

Abstract: Previous functional magnetic resonance imaging (fMRI) studies have demonstrated digit somatotopy in primary somatosensory cortex (SI), and even shown that at high spatial resolution it is possible to resolve within-digit somatotopy. However, fMRI studies have failed to resolve the spatial organisation of digit representations in secondary somatosensory cortex (SII). One of the major limitations of high spatial resolution fMRI studies of the somatosensory system has been the long acquisition time needed to acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 34 publications
10
43
0
Order By: Relevance
“…For most of the participants, the forehead region of the somatosensory cortex lies deep within the postcentral sulcus in a region between the lower limb and upper limb area. This finding is consistent with a study on the facial representation on SI in macaques [21], as well as a recent fMRI study at 7 T which showed cortical activations in the same area upon cheek stimulation [35].…”
Section: Large Variability Observed In Individual Somatotopic Mapssupporting
confidence: 92%
See 2 more Smart Citations
“…For most of the participants, the forehead region of the somatosensory cortex lies deep within the postcentral sulcus in a region between the lower limb and upper limb area. This finding is consistent with a study on the facial representation on SI in macaques [21], as well as a recent fMRI study at 7 T which showed cortical activations in the same area upon cheek stimulation [35].…”
Section: Large Variability Observed In Individual Somatotopic Mapssupporting
confidence: 92%
“…As seen in Table [cortical mag] the pial surface area of voxels that were correlated with0. 35 to the finger stimulus timing was on the order of 10 cm2 for 4 out of 6 of the people scanned, nearly 25% of the total surface area of the postcentral gyrus and sulcus. For participant F, the surface area was about 15% less, while for participant D, the surface area was only 3 cm 2 .…”
Section: Large Variability Observed In Individual Somatotopic Mapsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted November 15, 2020. ; https://doi.org/10.1101/2020.11.12.379339 doi: bioRxiv preprint to consist of two separate regions: pre-SMA and SMA proper [35,36], which might each represent the whole body in full. The region denoted insula, which covers the region enclosed by the Sylvian fissure up to the parietal operculum, likely contains the secondary somatosensory cortex (S2), which is believed to contain a whole-body somatotopy as well [37][38][39]. The selection of regions of interest (ROI) often is an arbitrary and non-trivial process, which could be aided in future studies by the current pRF center results.…”
Section: Prf Center and Sizementioning
confidence: 99%
“…It was considered the methodologically most appropriate alternative to have exact the same set up for both groups except of varying the administration of the stimulation protocol. A control stimulation at the same hand was excluded since it could still have interfered with the relevant stimulation site due to potentially overlapping cortical representations (Ackerley & Kavounoudias, ; Kalberlah et al, ; Sanchez Panchuelo, Besle, Schluppeck, Humberstone, & Francis, ). Conducting the control stimulation on the other hand was also not an option because transcallosal connections between homologous somatosensory regions as well as nonhomologous regions (Tamè, Braun, Holmes, Farnè, & Pavani, ) could have a potential effect on the results.…”
Section: Methodsmentioning
confidence: 99%